2011
DOI: 10.1155/2011/205437
|View full text |Cite
|
Sign up to set email alerts
|

Omental Evisceration after Cesarean Section: Safety of Peritoneal Nonclosure Technique

Abstract: A case of omental prolapse presented to us on the fifteenth postoperative day following an uneventful Cesarean section. A rare complication as such questions the safety of peritoneal nonclosure that has been adopted by obstetricians in recent times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…Two similar cases reported in literature of omental prolapse in cases of Misgav Ladach technique in 2004 and 2011 by Scholz et al, and Bhattacharya et al reported, respectively, omental herniation in post LSCS case on days 7 and 15 were managed similarly like in our case with laparotomy. [5,6] In other few cases, omentum was sutured between the edges of fascia recti. [7,8] The mass might had been present earlier, which was probably missed by the intern during change of dressing.…”
Section: Case Reportmentioning
confidence: 99%
“…Two similar cases reported in literature of omental prolapse in cases of Misgav Ladach technique in 2004 and 2011 by Scholz et al, and Bhattacharya et al reported, respectively, omental herniation in post LSCS case on days 7 and 15 were managed similarly like in our case with laparotomy. [5,6] In other few cases, omentum was sutured between the edges of fascia recti. [7,8] The mass might had been present earlier, which was probably missed by the intern during change of dressing.…”
Section: Case Reportmentioning
confidence: 99%